2004
DOI: 10.1002/chem.200305745
|View full text |Cite
|
Sign up to set email alerts
|

Yttrium and Lanthanide Diphosphanylamides: Syntheses and Structures of Complexes with one {(Ph2P)2N} ligand in the Coordination Sphere

Abstract: Treatment of the recently reported potassium salt [K(thf)(n)][N(PPh(2))(2)] (n=1.25, 1.5) with anhydrous yttrium or lanthanide trichlorides in THF leads after crystallization from THF/n-pentane (1:2) to the monosubstituted diphosphanylamide complexes [LnCl(2)[(Ph(2)P)(2)N](thf)(3)] (Ln=Y, Sm, Er, Yb). The single-crystal X-ray structures of these complexes show that the metal atoms are surrounded by seven ligands in a distorted pentagonal bipyramidal arrangement, in which the chlorine atoms are located in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 47 publications
3
29
0
Order By: Relevance
“…[50] So far, few COT lanthanum complexes were structurally characterized. The approximate La-Ct distances for (COT)La(η 5 -C 5 Me 4 H)(thf) 2 (2.099 Å), [51] (COT)La(η 5 -C 4 H 7 OCH 2 C 5 H 4 )(thf) (2.067 Å), [52] and O (2.047 Å) [13] appear slightly elongated compared to compound 2 (2.025 Å).…”
Section: Synthesis and Characterization Of Cot/iodide Complexesmentioning
confidence: 91%
See 2 more Smart Citations
“…[50] So far, few COT lanthanum complexes were structurally characterized. The approximate La-Ct distances for (COT)La(η 5 -C 5 Me 4 H)(thf) 2 (2.099 Å), [51] (COT)La(η 5 -C 4 H 7 OCH 2 C 5 H 4 )(thf) (2.067 Å), [52] and O (2.047 Å) [13] appear slightly elongated compared to compound 2 (2.025 Å).…”
Section: Synthesis and Characterization Of Cot/iodide Complexesmentioning
confidence: 91%
“…J. and formation of compound R (Figure 2) was achieved straightforwardly. [13] Figure 2. Structurally characterized COT Ln III complexes with monoanionic N-donor ligands Q, [4] R, [13] S, [32] T, [32] U, [4] V, [12] W, [14,33] X.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The P(1)···Y(1) distance of 3.2575(6) in 4 is less than 7 % longer than the longest reported YÀP bond length of 3.045(2) , [29] although shorter YÀP bond lengths are more typical. [18,30] In comparison, the P(1)···Gd(1) distance of 3.2440(9) in 5 is actually shorter than the P(1)···Y(1) distance in 4, which can be rationalised by the slightly larger size of the Gd III ion requiring a greater strain in the ancillary ligand fro its accommodation. This assertion is confirmed by the slightly larger sum of C-P-C angles in 5 than in 4, which are 326.70(26) and 324.69(17)8, respectively.…”
Section: Synthesis Of Heterobimetallic Complexesmentioning
confidence: 90%
“…The single crystal X-ray structure revealed that both complexes 32 and 33 adopt a four-legged piano-stool conformation [46]. [46].…”
Section: H 8 )(Thf) 3 I] and [K(thf) N ][N(pph 2 ) 2 ] (Scheme 12)mentioning
confidence: 99%